2012
DOI: 10.1136/gutjnl-2011-301585
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic oral topotecan prolongs survival and reduces liver metastasis in improved preclinical orthotopic and adjuvant therapy colon cancer models

Abstract: ObjectiveAdvanced and recurrent diseases are the major causes of death in colon cancer. No standard preclinical model addresses advanced disease and spontaneous metastasis after orthotopic tumour growth. In this study, the authors report the establishment of such standardised orthotopic mouse models of colon cancer and their use in evaluating metronomic topotecan alone or in combination with standard chemotherapy.DesignHuman colon cancer cell lines, transfected with human chorionic gonadotropin and luciferase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 50 publications
1
74
0
Order By: Relevance
“…SK-OV-3 is a human ovarian cancer cell line (ATCC number: HTB-77). HT29hCG-Luc is a human colon cancer cell line (ATCC number: HTB-38) kindly provided by Dr. C. Hackl [15]. MSTO-211h is a human mesothelioma cancer cell line (ATCC number: CRL-2081).…”
Section: Cell Linesmentioning
confidence: 99%
“…SK-OV-3 is a human ovarian cancer cell line (ATCC number: HTB-77). HT29hCG-Luc is a human colon cancer cell line (ATCC number: HTB-38) kindly provided by Dr. C. Hackl [15]. MSTO-211h is a human mesothelioma cancer cell line (ATCC number: CRL-2081).…”
Section: Cell Linesmentioning
confidence: 99%
“…It is worth to mention that the overwhelming number of ectopic transplantation models do not mimic the human counterpart with respect to tumor vascularization, tumor microenvironment, metastatic spread to the relevant distant sites, or responsiveness toward chemotherapeutics and other drugs (37). Cell transplantation into the organ of origin, the orthotopic transplantation, is rarely done, although it resembles much better the human situation with respect to the tumor microenvironment or cancer metastasis However, depending on the context, this assay needs advanced technical skills (38).…”
Section: Cell-based Transplantation Modelsmentioning
confidence: 99%
“…This emerging approach has been extensively evaluated in clinical trials and animal models 1. Hackl et al 2 report for the first time that metronomic oral topotecan therapy in adjuvant and metastatic settings prolongs survival and reduces liver metastasis in mouse models of metastatic CRC. Their findings provide a rational for clinical trials of metronomic oral topotecan in CRC at stage III and metastatic CRC as well.…”
mentioning
confidence: 99%
“…However, the efficacy of metronomic oral topotecan is not known in CRC. In this issue of Gut , Hackl et al 2 examined the effects of metronomic oral topotecan plus pazopanib and/or tegafur-uracil in mouse metastatic models of CRC and found that metronomic oral topotecan significantly prolonged survival by inhibiting primary tumours and liver metastasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation